Avaliação dos efeitos da terapia celular em modelo experimental de dor neuropática - Almeida, Taís Adelita Morais de (2010)
Neuropathic pain is caused by dysfunction of the nervous system and affects about 5% of the world. Its control is still inefficient and only a third of patients undergoing therapy existing features more than 50% pain relief. This study investigated the potential of cell therapy for recovery from nervous system function in experimental neuropathic pain. We use the model of partial sciatic nerve ligation in mice and evaluated the mechanical allodynia with von Frey filaments. Mice were treated intravenously with mononuclear cells obtained from bone marrow (BMMC), soluble factors resulting from the lysate of these cells and cell populations of the same origin adherent and non-adherent to polymers. Treatment with BMMC was also administered to animals for the gene knockout of the cytokine IL-10. Levels of cytokines IL-1β, IL-6, IL-10 and TNF-α were measured in sections of the sciatic nerve and spinal cord. The markup for GFAP in Schwann cells was evaluated in experimental groups. As a result, the administration of BMMC reduced allodynia and the expression of cytokines typically pro-inflammatory IL-1β and TNF-α, with increased expression of anti-inflammatory cytokine IL-10 in sciatic nerve and spinal cord. In knockout animals IL-10 treatment was ineffective. In addition, animals treated with BMMC showed a lower number of Schwann cells, involved in the production of noxious factors in the sciatic nerve. These results emphasize the potential of cell therapy for neuropathic pain management with the participation of soluble factors, mainly IL-10.